On the influence of tungsten impurities on the transport properties of thermal plasma - Porytskyy, P.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The influence of tungsten impurities on the transport properties of thermal plasma is considered in the ambient atmosphere of argon. The calculations are carried out on the base of Grad’s method, and it is shown that a small amount of tungsten causes the essential changes in the values of transport coefficients in comparison with the case of pure argon. It is revealed that the influence of the Ramsauer effect on transport properties can be neutralized by additions of metal into ambient argon. Рассмотрено влияние примесей вольфрама на транспортные свойства термической плазмы в атмосфере аргона. Проведенные расчеты основывались на методе моментов Грэда. Показано, что незначительное количество примесей вольфрама может существенно изменить величины транспортных коэффициентов в сравнении со случаем чистого аргона. Показана возможность нейтрализации влияния эффекта Рамзауэра на свойства плазмы путем добавки металлических примесей. Розглянуто вплив домішок вольфраму на транспортні властивості термічної плазми в атмосфері аргону. Проведені розрахунки ґрунтувалися на методі моментів Ґреда. Показано, що невелика кількість домішок вольфраму може суттєво змінити величини транспортних коефіцієнтів порівняно із випадком чистого аргону. Висвітлено можливість нейтралізації впливу ефекта Рамзауера на властивості плазми шляхом додавання металевих домішок.